2020
DOI: 10.3390/biology9080217
|View full text |Cite
|
Sign up to set email alerts
|

Diatoms for Carbon Sequestration and Bio-Based Manufacturing

Abstract: Carbon dioxide (CO2) is a major greenhouse gas responsible for climate change. Diatoms, a natural sink of atmospheric CO2, can be cultivated industrially in autotrophic and mixotrophic modes for the purpose of CO2 sequestration. In addition, the metabolic diversity exhibited by this group of photosynthetic organisms provides avenues to redirect the captured carbon into products of value. These include lipids, omega-3 fatty acids, pigments, antioxidants, exopolysaccharides, sulphated polysaccharides, and other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 182 publications
(255 reference statements)
0
7
0
1
Order By: Relevance
“…It has previously been shown that biomass productivities up to 146 tons dry cell weight (dcw) ha −1 y −1 in small scale cultivations and 60-75 tons dcw ha −1 y −1 in mass cultivations are possible (Sethi et al, 2020). It is important in the Microalgae Biotechnology sector to develop novel species/strains and production platforms.…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been shown that biomass productivities up to 146 tons dry cell weight (dcw) ha −1 y −1 in small scale cultivations and 60-75 tons dcw ha −1 y −1 in mass cultivations are possible (Sethi et al, 2020). It is important in the Microalgae Biotechnology sector to develop novel species/strains and production platforms.…”
Section: Introductionmentioning
confidence: 99%
“…[ 7,30,31,54,60 ] Moreover, reports have highlighted optimal conditions for EPA and fucoxanthin production in P. tricornutum ; using different irradiances [ 8,30 ] and CO 2 concentrations. [ 61–64 ] The overall conclusion from these studies highlights that at lower light intensities (30–60 μmol m −2 s −1 ), optimal temperature, that is, 24°C, 1% CO 2 , 20% salinity, and higher nitrate concentrations (NaNO 3 – 300 mg L −1 ) leading to improved EPA and fucoxanthin yields. Such studies provide insights for testing similar combinations in mixotrophy for large‐scale diatom farming.…”
Section: Discussionmentioning
confidence: 93%
“…содержания углерода в атмосфере Так как диатомовые водоросли являются фотосинтезирующими организмами, несомненно, немаловажное значение для их развития имеет концентрация двуокиси углерода в атмосфере Земли. Они считаются биогеохимически значимой группой фитопланктона, которая вносит значительный вклад в естественное поглощение углерода (Armbrust, 2009), и предлагаются даже как возможное решение проблемы повышения уровня CO 2 в атмосфере (Sethi et al, 2020).…”
Section: влияние на скорость репродукции диатомейunclassified